Penerapan Functional Family Therapy Dalam Menurunkan Perilaku Bermasalah Remaja - Firdasannah, Astri; Tarigan, Alna Aulia; Khoirunisa, Amalia; Hermawan, Cyndi Fiolandha; Marlianda, Dinda; Ashari, Rizqia Joanesa (LPPM Universitas Informatika dan Bisnis Indonesia, 2024)
In order to address problematic teenage behavior, the Indonesian version of the Functional Family Therapy (FFT) module was developed based on the FFT intervention developed by Sexton and Alexander in the United States since 2002. The purpose of this study is to ascertain whether using FFT based on the module will lessen problematic conduct in teenagers who are Correctional Center Client (CCC) clients. The measurement tools used are the Strength and Difficulties Questionnaire (SDQ, Indonesian version) and the Egna Minnen Beträffande Uppfostran-Children (EMBU-C) adapted into Indonesian to determine the type of parenting style perceived by adolescents towards their fathers and mothers. The results of this test indicate the influence of implementing FFT in reducing problematic behavior in adolescents. The implications of this research to serve as a starting point in adding references for therapy program interventions for BAPAS Bandung and will continue to be developed in Indonesia.